It's the political economy, stupid the global financial crisis in art and theory - Sholette, Gregory; Ressler, Oliver (Pluto Press, 2013)
It's the Political Economy, Stupid brings together internationally acclaimed artists and thinkers, including Slavoj Žižek, David Graeber, Judith Butler and Brian Holmes, to focus on the current economic crisis in a sustained and critical manner. In sympathy with the subject matter, the book features powerful original artwork for the cover, and an internal design theme based on the movements of Goldman Sachs stock market values by activist designer Noel Douglas. What emerges is a powerful critique of the current capitalist crisis through an analytical and theoretical response and an aesthetic-cultural rejoinder. By combining artistic responses with the analysis of leading radical theorists, the book expands the boundaries of critique beyond the usual discourse. It's the Political Economy, Stupid argues that it is time to push back against the dictates of the capitalist logic and, by use of both theoretical and artistic means, launch a rescue of the very notion of the social.